Hitting Net-Zero Without Stopping Flying: Increasing Air Travelers' Likelihood to Opt-in to Voluntary Carbon Offsetting. (January 2023) - Liu, Yi; Jiang, Qiqi; Gleasure, Rob
Voluntary carbon offset (VCO) programs give air travelers opportunities to neutralize their carbon footprint. Despite its potential, few existing studies have explained how to present VCOs that can effectively appeal to the sensibilities of travelers in different conditions. We designed three online experiments with strategies to motivate travelers to opt-in. We found travelers who receive concrete messages that emphasize specific actions are more likely to opt-in to VCOs when flying in the near future. In contrast, travelers receiving abstract messages that emphasize general initiatives are more likely to opt-in to VCOs when flying in the distant future. When travelers are allowed to choose their preferred carbon offset method, they are more likely to opt in, especially when they receive concrete messages that indicate specific actions but not general initiatives. These findings contribute to the aviation carbon offset literature and offer useful new insights for airline companies.